MINDFULNESS AND CHANGE READINESS IN ORGANIZATIONS – A CORRELATIONAL STUDY - Pantula, Lekha (International Journal of Psychosocial Rehabilitation, 2020)
Change in organizations lays the foundation for long-term success, and hence, it should be embraced rather than feared. It is not only important to adapt to changes but also to thrive, develop, and operate more efficiently and cost-effectively. Overall, some of the benefits of organizational change include superior productivity, reduced costs, improved quality, greater revenue, enhanced efficiency, and operational excellence. Evidence shows that mindfulness is associated with outcomes of enhanced psychological and physiological well-being. There are very few studies that talk about the relationship between mindfulness and change, and almost none with regard to mindfulness and change readiness in organizations. Although studies have been done on various other variables such as motivation, job satisfaction, leadership, teamwork, etc., none of them have tried to establish a direct link between both the variables. Through the administration of standardized questionnaires to a sample population of 103 participants from different organizational backgrounds, this study aims to establish a correlation between the variables of mindfulness and change readiness and check for gender differences in both.